Defisiensi mikronutrien pada anak usia 12-59 bulan di Desa Lebih, Kabupaten Gianyar, Bali - Ni Ketut Sutiari; Ni Made Utami Dwipayanti; Putu Ayu Swandewi Astuti; Kadek Nuansa Putri Wulandari; Widya Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Deficiency of micronutrients in children of age 12-59 months in Lebih Village, Gianyar District, BaliBackground: Lack of food intake, either in quantity or quality, will continuously cause children to get sick easily, such as being susceptible to infectious diseases and ultimately inhibiting the children’s growth.Objective: This study aimed to describe the status of micronutrients (zinc and iodine) and anemia status among children aged 12-59 months in Lebih Village. Methods: This analytic observational study used a cross-sectional design conducted in Lebih Village, Gianyar Regency. The study population was all children under five aged 12-59 months. In addition, 91 children under five were selected as research subjects using the probability proportional to size method. The data collected were the identity of the subjects (children under five and their mothers) using the interview method, serum zinc levels, urinary iodine excretion (EIU) levels, and Hb levels. Results: The results showed that the subjects’ mean age was 37.0±13.3 months, and most subjects (54.9%) were male. The biochemical examination showed that the mean serum zinc levels, the median urine iodine levels, and the mean Hb levels were 72.5±6.3 g/dL, 78.5 g/L, and 12.7±1.8 g/dL, respectively. 17.6% of the subjects had anemia, 14.3% had zinc deficiency, and 60.4% had iodine deficiency. Conclusion: Children under five aged 12-59 months in Lebih Village had micronutrient deficiencies such as zinc, iodine, and iron.